FLOOD FACTORS AND HANDLING: CASE STUDY OF INDONESIA AND THE PHILIPPINES - Oot Hotimah; Edies Adelia; Maulida Musoffa; Shinta Debora (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Flooding is a natural phenomenon that can cause disasters for humans, especially in Indonesia and the Philippines, which often experience significant impacts on the economy, transportation, and social life. This research aims to analyze the factors that cause flooding in both countries, compare the management policies implemented, and provide recommendations for improved mitigation. The method used is a literature review to collect and analyze various scientific sources. The results show that in Indonesia, factors causing flooding include land subsidence, land use change, and climate change, while in the Philippines, flooding is often triggered by tropical storms and extreme rainfall. Indonesia's response strategy focuses on river normalization and drainage infrastructure, while the Philippines implements a National Disaster Risk Reduction and Management Plan that covers prevention, preparedness, and rehabilitation. Despite these efforts, challenges such as urbanization and land acquisition still hamper the effectiveness of flood management. Recommendations include improving infrastructure, sustainable spatial planning, and community education.